2015
DOI: 10.1210/jc.2014-3925
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Advanced Glycation Endproducts in Obese Indicate Risk for the Metabolic Syndrome: A Link Between Healthy and Unhealthy Obesity?

Abstract: High sAGEs, a modifiable risk factor for IR, may indicate risk for the MS, type 2 diabetes, and cardiovascular disease. High dietary AGE consumption and serum AGE levels may link healthy obesity to at-risk obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 41 publications
5
98
3
1
Order By: Relevance
“…Suggested links include chronic inflammation, mitochondrial dysfunction,, Th17-induced neutrophilia, macrophage dysregulation, hormonal changes, lipid metabolism, insulin resistance, and body mechanics (Baffi et al, 2016; Chesne et al, 2014; Shore and Cho, 2016). Other well-described abnormalities in obesity and metabolic syndrome, accelerated formation of advanced glycation end products (AGEs) and alterations in arginine metabolism may also play a crucial role in asthma pathogenesis and may be modulated by the anti-inflammatory incretin, GLP-1 (Figure 1) (Holguin, 2013; Milutinovic et al, 2012; Ojima et al, 2013; Singh et al, 2015; Uribarri et al, 2015). …”
Section: Obesity-related Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Suggested links include chronic inflammation, mitochondrial dysfunction,, Th17-induced neutrophilia, macrophage dysregulation, hormonal changes, lipid metabolism, insulin resistance, and body mechanics (Baffi et al, 2016; Chesne et al, 2014; Shore and Cho, 2016). Other well-described abnormalities in obesity and metabolic syndrome, accelerated formation of advanced glycation end products (AGEs) and alterations in arginine metabolism may also play a crucial role in asthma pathogenesis and may be modulated by the anti-inflammatory incretin, GLP-1 (Figure 1) (Holguin, 2013; Milutinovic et al, 2012; Ojima et al, 2013; Singh et al, 2015; Uribarri et al, 2015). …”
Section: Obesity-related Asthmamentioning
confidence: 99%
“…AGEs can also be consumed from foods prepared with intense heat (such as baking or frying). Serum AGEs are markers of insulin resistance and inflammation, and elevated levels may distinguish metabolic syndrome from obesity (Uribarri et al, 2015). …”
Section: Advanced Glycation End-products and Their Receptormentioning
confidence: 99%
“…Here, the biochemical data did not correlate with the clinical scores, suggesting that there could exist a clinical threshold from which these biomarkers may predict the development of the disease. Accordingly, Uribarri et al [4] suggested that more specific and sensitive biomarkers are needed to identify healthy from unhealthy obese subjects. Figure 1 B and C show that AGEs levels were unexpectedly reduced in the blood from class III obese subjects, and the losartan/metformin therapy did not induce any alterations.…”
Section: Findings/discussionmentioning
confidence: 99%
“…For example, the risk for obese individuals to develop type 2 diabetes or a heart attack has already been linked to blood markers of inflammation [3] and of glycotoxicity [4]. Here, we investigated whether markers of inflammation, including high-sensitive c reactive protein and neopterin levels, and markers of sustained hyperglycemia, such as, glycated hemoglobin and advanced glycation end products (AGEs), correlated with HOMA-IR (homeostasis model assessment-insulin resistance), LAP (lipid accumulation product, which predicts the incidence of cardiovascular diseases; blood and the anthropometric marker) and the Framingham score (estimates risk of heart attack in ten years) in class III obese Brazilian individuals.…”
Section: Issn: 2056-8827mentioning
confidence: 99%
“…After the ingestion of an unhealthy diet, AGEs can get absorbed in the gastrointestinal tract [42,71] and then get deposited in various tissues including the ovaries. Approximately 10% of the ingested AGEs are transported into circulation: one third of which is excreted by the kidneys while two-thirds linger in the body and bind to several tissues [72].…”
Section: Ages and Their Two Receptors Rage And Sragementioning
confidence: 99%